A20 Establishes Negative Feedback With TRAF6/NF-κB and Attenuates Early Brain Injury After Experimental Subarachnoid Hemorrhage - Deng, Hong-Ji; Deji, QuZhen; Zhaba, WangDui; Liu, Jia-Qiang; Gao, Sheng-Qing; Han, Yan-Ling; Zhou, Meng-Liang; Wang, Chun-Xi (Frontiers in Immunology, 2021)
Nuclear factor (NF)-κB–ty -50mediated neuroinflammation plays a crucial role in early brain injury (EBI) after subarachnoid hemorrhage (SAH). As an important negative feedback regulator of NF-κB, A20 is essential for inflammatory homeostasis. Herein, we tested the hypothesis that A20 attenuates EBI by establishing NF-κB–associated negative feedback after experimental SAH. In vivo and in vitro models of SAH were established. TPCA-1 and lentivirus were used for NF-κB inhibition and A20 silencing/overexpression, respectively. Cellular localization of A20 in the brain was determined via immunofluorescence. Western blotting and enzyme-linked immunosorbent assays were applied to observe the expression of members of the A20/tumor necrosis factor receptor-associated factor 6 (TRAF6)/NF-κB pathway and inflammatory cytokines (IL-6, IL-1β, TNF-α). Evans blue staining, TUNEL staining, Nissl staining, brain water content, and modified Garcia score were performed to evaluate the neuroprotective effect of A20. A20 expression by astrocytes, microglia, and neurons was increased at 24 h after SAH. A20 and inflammatory cytokine levels were decreased while TRAF6 expression was elevated after NF-κB inhibition. TRAF6, NF-κB, and inflammatory cytokine levels were increased after A20 silencing but suppressed with A20 overexpression. Also, Bcl-2, Bax, MMP-9, ZO-1 protein levels; Evans blue, TUNEL, and Nissl staining; brain water content; and modified Garcia score showed that A20 exerted a neuroprotective effect after SAH. A20 expression was regulated by NF-κB. In turn, increased A20 expression inhibited TRAF6 and NF-κB to reduce the subsequent inflammatory response. Our data also suggest that negative feedback regulation mechanism of the A20/TRAF6/NF-κB pathway and the neuroprotective role of A20 to attenuate EBI after SAH.